miR-21 Is a Promising Novel Biomarker for Lymph Node Metastasis in Patients with Gastric Cancer - Yuejuan Xu; Jue Sun; Jianhua Xu; Qi Li; Yuewu Guo; Qiang Zhang (Gastroenterology Research and Practice)
Background. Gastric cancer (GC) is an important malignant disease around the world. Abnormalities of microRNAs (miRNAs) have been implicated in carcinogenesis of various cancers. In the present study, we examined miR-21 expression in human gastric cancer with lymph node metastasis and attempted to uncover its relationship with clinicopathologic data, especially with lymph node metastasis. Materials and Methods. The expression levels of miR-21 in the tumor specimens of GC patients were quantified by RT-PCR. The correlation between miR-21 level and multiple clinicopathological factors was then examined by Mann-Whitney test, Kaplan-Meier survival analysis, and operating characteristic (ROC) analysis. Results. The expression level of miR-21 was higher in GC patients with lymph node metastasis than in those without lymph node metastasis (P<0.05). Expression level of miR-21 was significantly correlated with histologic type, T stage, lymph node metastasis and pTNM stage. The overall survival rates in GC patients with low upregulated miR-21 expression were significantly higher than those with high upregulated miR-21 (P<0.05). Conclusion. A close association is implicated between the elevated miR-21and lymph node metastasis, which could potentially be exploited as a practical biomarker for lymph node metastasis in patients with GC.